2008
DOI: 10.1111/j.1365-2184.2008.00566.x
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Role of α7‐nicotinic acetylcholine receptor in human non‐small cell lung cancer proliferation

Abstract: These results showed that alpha7-nAChR plays an important role in NSCLC cell growth and tumour progression as well as in cell death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
60
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(66 citation statements)
references
References 52 publications
5
60
1
Order By: Relevance
“…While all classes of nAChRs are capable of desensitization through chronic agonist exposure, there are definite immediate effects of nicotine on nAChRs in a subunitdependent manner. Although it is currently unknown whether chronic exposure of nAChR to nicotine via E-Cigs can cause lung cancer, the role of nAChR ␣7 in contributing to nonsmall cell lung cancer by altering cell proliferation and apoptotic resistance has been reported (86,113).…”
Section: Will Nicotine and Chemical Constituents In E-liquids/e-cigs mentioning
confidence: 99%
“…While all classes of nAChRs are capable of desensitization through chronic agonist exposure, there are definite immediate effects of nicotine on nAChRs in a subunitdependent manner. Although it is currently unknown whether chronic exposure of nAChR to nicotine via E-Cigs can cause lung cancer, the role of nAChR ␣7 in contributing to nonsmall cell lung cancer by altering cell proliferation and apoptotic resistance has been reported (86,113).…”
Section: Will Nicotine and Chemical Constituents In E-liquids/e-cigs mentioning
confidence: 99%
“…Multiple studies have shown that activation of nAChRs by nicotine, which is an exogenous ligand for nAChRs, stimulates tumor cells growth in breast, 17 lung, 18 colon, 19 bladder 20 and cervical cancer. 21 The muscarinic receptors (mAChRs) are G-protein-coupled receptors, and 5 subtypes of mAChRs (M1-M5) have been identified.…”
Section: Introductionmentioning
confidence: 99%
“…While nAChRs are mainly expressed in neurons and neuromuscular junctions, they are also present on a variety of nonneuronal cells, where they induce cell proliferation, invasion, and angiogenesis (16,19,20,36,53,67). While there is scant evidence that nicotine contributes to the initiation of tumors, it has been demonstrated that nicotine can promote the growth and metastasis of solid tumors in vivo (10,44), suggesting that nicotine might be promoting the progression of tumors already initiated by the tobacco-specific nitrosamines (10).…”
mentioning
confidence: 99%